Job stress and burnout among social workers in the VUCA world of COVID-19 pandemic - Gabriela Dima, Luiza Meseșan Schmitz, Marinela-Cristina Șimon (Sustainability, 2021)
This paper aimed to explore the changes posed by the new COVID-19 pandemic to the field of social work and its impact on social workers in terms of job stress and burnout in Romania. Two conceptual models were used to frame the discussion: the theoretical framework of VUCA (volatility, uncertainty, complexity, and ambiguity) to discuss the challenges that the unprecedented context of the COVID-19 pandemic has created for social workers; and the Job Demands and Resources model (JD-R) to understand job demands perceived as stressors and burnout. Based on convergent mixed methods, the study sample consisted of 83 social workers employed in statutory and private social services in Romania, from different areas of intervention. Results showed that social workers perceived a high level of job stress related to work during the pandemic, which was associated with higher levels of burnout in the areas of personal burnout (average score 55.9) and work-related burnout (average score 52.5). Client-related burnout was lower (average score 38.4), indicating that stress was generated mainly by organisational factors and work-related factors (workload, aligning to new legislative rules and decisions, inconsistency, instability, ambiguity of managerial decisions, and lack of clarity of working procedures) and less by client-related stressors (lack of direct contact with clients, risk of contamination, managing beneficiaries’ fears, and difficulties related to technology). High job demands and limited job resources (managerial and supervisory support, financial resources, and recognition and reward) led to a high to very high level of work-related burnout for 15.7% and an upper-medium level for 44.2% of respondents. A group of 27.7% reported lower to medium levels of work-related burnout, while 14.5% had very low levels, managing to handle stress factors in a healthy manner. Study results pointed to the importance of organisational support and the development of a self-care plan that help to protect against job stress and burnout. Recommendations were made, putting forward the voice of fieldworkers and managers fostering initiatives and the application of sustainability-based measures and activities designed to deal with the challenges of the VUCA environment.
Keywords: COVID-19; social work/er; job stress; burnout; VUCA